Possibility of Producing bioethanol from Moringa oleifera Press Cake - Ali, Eman N.; Umarul, I. A. (2015)
To introduce a new biomass for producing bioethanol, Moringa oleifera press cake was considered in this research work. Moringa oleifera belongs to Moringacae family; it is called horseradish, tree of life, or miracle tree due to the of all parts of the tree for many purposes. Moringa oleifera press cake is the by-product of oil extraction from the seeds and can be considered for bioethanol production which offers an environmnetally friendly biofuel.